1993
DOI: 10.1172/jci116685
|View full text |Cite
|
Sign up to set email alerts
|

Insulin attenuates agonist-mediated calcium mobilization in cultured rat vascular smooth muscle cells.

Abstract: Insulin has been shown to attenuate pressor-induced vascular contraction, but the mechanism for this vasodilatory action is unknown. This study examines the effect of insulin on angiotensin II (ANG II)-induced increments in cytosolic calcium in cultured rat vascular smooth muscle cells (VSMC). 20-min incubations with insulin (10 ,U/ml to 100 mU/ml) did not alter basal intracellular calcium concentration (ICa2I,), but inhibited the response to 100 nM ANGII in a dose-dependent manner (ANG II alone, 721±54 vs. AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 55 publications
4
38
0
5
Order By: Relevance
“…VSMCs were isolated from rat thoracic aorta (male Sprague-Dawley rats, 250 to 300 g) by enzymatic dispersion 10,24 and grown in a 1:1 mixture of Dulbecco's modified Eagle's medium and Ham's F-12 (Sigma Chemical Co) supplemented with 10% fetal calf serum (FCS, Tissue Culture Biologicals), 50 U/mL penicillin, and 50 g/mL streptomycin (Sigma). Confluent cultures were passaged after treatment with trypsin-EDTA and reseeding at a 1:4 ratio in fresh media.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…VSMCs were isolated from rat thoracic aorta (male Sprague-Dawley rats, 250 to 300 g) by enzymatic dispersion 10,24 and grown in a 1:1 mixture of Dulbecco's modified Eagle's medium and Ham's F-12 (Sigma Chemical Co) supplemented with 10% fetal calf serum (FCS, Tissue Culture Biologicals), 50 U/mL penicillin, and 50 g/mL streptomycin (Sigma). Confluent cultures were passaged after treatment with trypsin-EDTA and reseeding at a 1:4 ratio in fresh media.…”
Section: Cell Culturementioning
confidence: 99%
“…Cells (4 to 12 passages) were seeded into 100-mm (P100) culture dishes and reached confluence in 5 to 7 days. 10 Cell lines were randomly screened for smooth muscle actin expression by immunofluorescent staining with anti-rat smooth muscle actin (Enzo Diagnostics Inc) and fluorescence-conjugated rabbit anti-mouse IgG (Cappel Laboratories, Organon Teknica Corp).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Insulin seems to have mixed effects on calcium flux, with some investigators demonstrating attenuation of inward calcium currents in rat VSMC in response to arginine vasopressin (11) and angiotensin II (12), and others showing stimulation of calcium uptake (13). In this study, we examined the effect of insulin on calcification of rat VSMC, and on VSMC phosphate and calcium transport.…”
Section: Introductionmentioning
confidence: 99%
“…Results of studies of the effects of insulin on {Ca2+]; metabolism have been inconsistent. In animals, insulin has been reported to increase [Ca2±Jj (19,20), decrease [Ca2±]1 (21) or have no effect on it (22,23). In a human study, insulin has been reported not to change platelet [Ca2+]; of normotensive subjects in vitro and in vivo (24).…”
Section: Discussionmentioning
confidence: 95%